Economic Growth Model and Renewable Energy Utilization: Perspective of Natural Resources Management and Sustainable Development of the Gowa Regency Region South Sulawesi, Indonesia - Surya, Batara; Salim, Agus; Saleh, Haeruddin; Abubakar, Herminawaty; Suriani, Seri; Sose, Andi Tenry; Kessi, Andi Makkulawu Panyiwi (International Journal of Energy Economics and Policy, 2021)
Regional development coupled with economic growth requires support for the use of renewable energy to support sustainable management of natural resources and the environment. Furthermore, economic growth towards industrialization has an impact on increasing energy consumption. This study aims to analyze: (1) Economic growth work as a determinant of the use of renewable energy in supporting regional development; (2) The direct and indirect effects of economic growth, the effectiveness of natural resource utilization, and the use of renewable energy on improving the quality of the environment and the sustainability of regional development; (3) Formulating an economic growth model based on the use of renewable energy, natural resource management and sustainable regional development. This study uses a qualitative and quantitative approach sequentially. Data obtained through observation, in-depth interviews, surveys, and documentation. The results showed that economic growth followed by the use, of new and renewable energy had an impact on increasing the productivity of economic enterprises and a positive contribution to improving the quality of the environment. Gowa Regency’s future development orientation is oriented towards optimizing the regional economic base sectors, increasing the contribution of the strategic economic sector, effective use of natural resources, strengthening human resource capacity, ensuring the availability and distribution of energy services, increasing regional revenues, and optimizing sources of income new. Furthermore, future economic growth is oriented towards increasing people’s incomes, opening new jobs, equitable development, and improving people’s welfare. This study recommends that the use of renewable energy is an important aspect that needs to be considered in the formulation of development policies towards economic growth, natural resource management and sustainable regional development of the Gowa Regency South Sulawesi, Indonesia. Keywords: economic growth; renewable energy; environmental quality; regional productivity; sustainable development. JEL Classification: Q5 DOI: https://doi.org/10.32479/ijeep.11676